MiR-140 targets Wnt1 to inhibit the proliferation and enhance drug sensitivity in osteosarcoma cells - Zhi, Wang; Feng, Qu; Mingzhu, Zhang (Cellular and Molecular Biology, 2022)
MicroRNAs (miRNAs) have been documented to function differently in numerous human cancers. Our study planned to investigate the role of microRNA-140 (miR-140) and to identify its possible target in osteosarcoma (OS) to predict their mechanism in OS. The miR-140 was down-regulated in OS, and its high expression decreased MG63 cell proliferation. At the molecular level, Wnt1 was a target of miR-140, and its expression could be suppressed by miR-140. Besides, miR-140 overexpression decreased drug resistance in OS cells treated by doxorubicin. Collectively, overexpression of miR-140 may inhibit human OS cell proliferation and may enhance drug sensitivity by direct regulation of Wnt/β-catenin signaling.